PEMBERDAYAAN IBU RUMAH TANGGA MELALUI PENGEMBANGAN BERBAGAI OLAHAN PISANG DI KELURAHAN MURUNG RAYA: PEMBERDAYAAN IBU RUMAH TANGGA MELALUI PENGEMBANGAN BERBAGAI OLAHAN PISANG DI KELURAHAN MURUNG RAYA - Nurul Hidayah; Maya Rezeki Angriani; Ridha Nur Izzat; Lisa Norsari; Nurhayati (Community Development Journal, 2021)
A preliminary survey showed that most women in Murung Raya Village managed banana processed products to help their husbands improve family income. It makes the products a superior product at Murung Raya Village. However, the targeted community lacked economic development, especially in brand design, marketing management, packing, and entrepreneurship management. This Community Service Activity aims to increase productive economic groups' knowledge, skill, and participation in the targeted community. The method used a community empowerment approach through discussion, training, and mentoring in economic development, especially entrepreneurship and business management. This paper used descriptive qualitative analysis with a checklist instrument. The result showed increased success indicators, especially in knowledge, skills in product management, packaging, online marketing, and familyincome. In conclusion, community empowerment through the economic development of processed bananas products increases knowledge, skills, and productive economic groups' participation in developing products with added value